Development of pop-up book to improve ethnic diversity learning for grade V elementary students - Ayu Fitria Ningsih; Eka Titi Andaryani (Jurnal Prima Edukasia, 2026)
Learning in Pancasila Education at the elementary school level tends to be less varied and has not fully supported the improvement of student learning outcomes due to the limited use of innovative learning media. This study aims to develop a Pop-Up Book learning medium with the theme of ethnic diversity, examine its feasibility, and determine its effectiveness in improving the learning outcomes of fifth-grade students. This study employs a research and development design involving 29 fifth-grade students, a classroom teacher, media experts, and material experts. Data are collected through learning outcome tests, observations, interviews, questionnaires, and documentation. The data are analyzed using qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistics, including normality tests, paired-sample t-tests, and N-gain analysis. The developed Pop-Up Book contains materials on ethnic diversity, including traditional houses, traditional clothing, traditional foods, and regional dances, supported by barcodes that provide additional examples. The results show that the media is considered highly feasible based on expert validation. The effectiveness test indicates a 25% increase in students’ learning outcomes between pretest and posttest scores, with N-gain results in the moderate category. In conclusion, the Pop-Up Book learning media is feasible and effective in improving students’ learning outcomes in Pancasila Education, particularly on ethnic diversity material. The findings imply that interactive and visually engaging media can serve as an alternative learning resource to enhance student participation and academic achievement in elementary schools.